Measurement of mechanical and physical properties of particleboard by hybridization of kenaf with rubberwood particles - Md. Tahir, Paridah; Abd Halip, Juliana; El-Shekeil, Yousuf Ali; Jawaid, Mohammad; Alothman, Othman Y. (Elsevier, 2014)
Kenaf is one of the potential raw materials available in Malaysia to use for particleboard manufacturing as an alternative solution to balance shortage of rubberwood (RW) supply. In this study, particleboard manufactured from kenaf stem (KS) and RW particle blends at different RW loading (0%, 50%, 70%, 100%) and resin levels (6%, 8%, 10%). Urea formaldehyde resin is used as a binder. The effects of RW:KS ratio and resin content on mechanical and dimensional stability properties of hybrid particleboard were determined. The results indicated that particleboards bonded with 10% resin level and 50:50 (RW:KS) had the highest strength (19.08 MPa) while particleboards made of 70:30 (RW:KS) display better stiffness (2.23 GPa). Statistical analysis using ANOVA and LSD were conducted on the obtained results. The results show that RW:KS ratio has greater influence over thickness swelling (TS) and water absorption (WA) of particleboard than the level of resin content. The relationship between internal bonding (IB) and TS of particleboards were also examined and obtained strong inverse relationship between IB and TS. Hybrid particleboards made from 70% RW and 30% KS with 10% resin content display over all good properties and comparable with 100% RW (control) samples. It concluded that kenaf stem can replace rubberwood particles up to 50% but the resin level must be kept at 10% or more because lower resin level (⩽8%) significantly decrease strength of the particleboard.